2008
DOI: 10.1785/gssrl.79.1.47
|View full text |Cite
|
Sign up to set email alerts
|

The High-Resolution Imaging (HRI) Portable Array: A Seismic (and Internet) Network Dedicated to Kilometric-scale Seismic Imaging

Abstract: International audienceWe have developed a network of portable seismic stations dedicated to the high resolution imaging of geological, potentially hazardous, targets. These targets - volcanoes, fault zones, landslide areas - are characterized by strong medium heterogeneities, rugged topography, rough field conditions, and require dedicated equipment in order to maximize the number of recording points. This new network is designed to a) operate experiments with a limited size crew, b) run on low power for possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The seismic data were acquired during three successive active surveys that took place between 2001 and 2007. Two different configurations where used: (i) a limited number (10) of standalone seismic stations recorded many small dynamite shots (100-300 g) fired along the 'Chemin des dames' trail around and on top of the dome, (ii) due to the weak signal noise ratio, we then deployed a large number of sensor using the High Resolution Imaging (HRI) facilities (Coutant et al 2008) along different profiles to record few large dynamite shots (1-4 kg) fired in 2 m deep holes. A total of 262 recordings sites and 106 shooting site ( Fig.…”
Section: Seismic Data and Traveltime Modellingmentioning
confidence: 99%
“…The seismic data were acquired during three successive active surveys that took place between 2001 and 2007. Two different configurations where used: (i) a limited number (10) of standalone seismic stations recorded many small dynamite shots (100-300 g) fired along the 'Chemin des dames' trail around and on top of the dome, (ii) due to the weak signal noise ratio, we then deployed a large number of sensor using the High Resolution Imaging (HRI) facilities (Coutant et al 2008) along different profiles to record few large dynamite shots (1-4 kg) fired in 2 m deep holes. A total of 262 recordings sites and 106 shooting site ( Fig.…”
Section: Seismic Data and Traveltime Modellingmentioning
confidence: 99%
“…Starting with George's 1955 mine gallery experiment 4 , muography has shown that this technique can derive the absolute average density of matter along the muon path and have visualized shallow crustal density distribution inside volcanoes 5 6 7 8 and fault zones 9 10 as well as archaeological objects 11 with better spatial resolution (in the order of a few m) than possible with the conventional techniques, including high resolution seismic tomography 12 13 . Muography can also be utilized to monitor temporal density variations inside large objects, due to, e.g., magma dynamics 14 and underground water table changes 15 , by taking advantage of the almost constant rate of muon flux arriving on Earth.…”
mentioning
confidence: 99%
“…A decametric resolution to resolve much finer details requires extremely high recording densities. Recently, Brenguier et al 30 conducted seismic tomography of a conical-shaped volcano with a base diameter of 1 km (approximately the size of Satsuma–Iwojima) and obtained a spatial resolution of 80 m by creating 400 seismic sources (370 sites for 16-ton vibrators and 30 sites for dynamite shots), having received the signals with a High Resolution Imaging Array 31 consisting of 258 seismic sensors. A tomographic measurement of this kind would be both economically and practically out of reach in the harsh field conditions in Satsuma–Iwojima.…”
Section: Resultsmentioning
confidence: 99%